Caracteristicas del consumo de ceftriaxona en el servicio neumologia del hospital almanzor aguinaga asenjo essalud durante el año 2007” - Pascual Alva, Patricia Xamin (2009)
The present study is of descriptive, transverse and retrospective type, which aim was to determine the characteristics of Ceftriaxona's consumption in Neumología's service during the year 2007 of the National Hospital Almanzor Aguinaga Asenjo, hospital of fourth level located in Chiclayo, Lambayeque's department. The population in study was constituted by the patients hospitalized in Neumología's service who were attended across the Drugstore of Unitary Dose from January 01 to December 31, 2007. One thought that 52.54 % of patients were treated by Ceftriaxona. Was observed that Ceftriaxona's major consumption was done by the masculine sex with 46.19 % and the interval of 60-year-old patients to more were those who received mainly this antibiotic in relation with the rest of groups. Ceftriaxona's major monthly consumption expressed in units registered was in September with 349 attended units, and Ceftriaxona's monthly average consumption, expressed in daily definite dose DDD/100 bed - days was of 23.94. In addition there was in study, which tends to diminish and finally there obtained an annual expense of S/.5734.14 nuevos soles, generated by Ceftriaxona's consumption in Neumología's service during the year 2007